Oral health in Russian young adults: A study on determinants of dental health, dental anxiety, and oral health-related quality of life in medical and dental students in North-West Russia - Drachev, Sergei N. (UiT The Arctic University of Norway, 2019)
Background: Dental caries and periodontal diseases are the most common oral diseases, affecting millions of people worldwide. These diseases are highly preventable; therefore any measures that promote oral health (OH) should be implemented at the community and individual level. Although programmes designed to prevent OH problems often focus on children, young adults aged 18-25 years are also an important target group for such programmes. Indeed, this age range comprises periods of biological, psychological, and social development and is a transition between adolescence and adulthood, when persons take responsibility for their health and may still change their health behaviour. Studying factors which may influence OH is extremely important to develop effective preventive programmes for young adults. In Russia, there is little information on OH and factors associated with OH in young adults. Thus, we conducted a study in a group of young medical and dental undergraduate students in North-West Russia. Objective: The study aimed to: i) investigate dental caries experience and determinants (socio-demographic factors, socioeconomic factors, and OH behaviour); ii) assess the prevalence of dental anxiety (DA) and to explore the association between DA and sociodemographic factors, socioeconomic factors, OH behaviour, general health, and OH; and iii) investigate how socio-demographic factors, socioeconomic factors, OH behaviour, selfreported OH characteristics, and clinically-assessed OH are related to OH-related quality of life (OHRQoL). Methods: This cross-sectional study included 474 medical and 333 dental undergraduate students of Russian nationality aged 18-25 years from the Northern State Medical University (NSMU), Arkhangelsk, North-West Russia. Information on socio-demographic factors, socioeconomic factors, OH behaviour, general health, and OH was obtained from a structured, self-administered questionnaire. Corah’s Dental Anxiety Scale (DAS) was applied to measure DA. OHRQoL was measured by the short version of ...